The performance of block codes in digital communication system / Nor Afzan Azmi - Azmi, Nor Afzan (2007)
Error control coding incorporates information into the signal that allows a receiver to find and correct bit error occurring in transmission and storage. Since such cording detects or corrects errors incurred in the communication or storage channel, it is often referred to as channel coding. [ 1] This project involves the design of a complete digital communication system. The objective is to first compare the performance of different type of channel without block code. The channels used are A WON channel, Multipath Rayleigh channel and Rician Fading channel. The second objective is to evaluate the performance of different type of block codes using A WON channel. AWON channel is selected because A WON channel is a good model for satellite and deep space communication link. It is not a good for most terrestrial links because of multipath, terrain blocking, interference, and other. However for terrestrial path modeling, A WON is commonly used to simulate background noise of the channel, in addition to multipath, terrain blocking, interference, ground clutter and self interference that modem radio systems encounter in terrestrial operation. The block codes that are covered are Hamming code and BCH code. For every different block codes the n-bit and k-bit parameters vary.